A systematic review on radiology services quality indicators - Almalki, Abdullah A.; Abdul Manaf, Rosliza; Juni, Muhamad Hanafiah; Kadir @ Shahar, Hayati; Mohd Noor, Noramaliza; Gabbad, Abdelsafi Abbas Mohammed (Community Health Society Malaysia, 2017)
Introduction: Services quality in radiology department became a concern of stakeholders. Quality of the service increases the consumer and provider benefits. Those benefits include services reputation improvement, increase loyalty, improve cost-effectiveness, and reduce dose of radiation. The aim of the study is to review related scientific articles that discussed radiology services indicators and to find out the gaps among those studies. Methods: A systematic search was performed utilising four electronic database which are, Pub-med, Science Direct, Medline and CINAHL using the keywords “radiology” and “indicators”. The included studies are those published until June of 2016, written in English, conducted on different diagnostic imaging sections and evaluated the quality of radiology services. Studies on therapeutic radiology, disease, pharmaceutical, or studies that examined technical effect of a particular equipment on a disease diagnosis were excluded. Results: A total of 33 scientific articles were identified. Of these, only 14 studies were eligible and included. Three of them discussed on discrepancy rate indicators, while two studies measured the repetition rate. Four discussed on report turnaround time, three was on dose of radiation, and the last was discussing on indicator and uses of them. Conclusion: Various types of indicators were used to measure quality in radiology services, mostly focussing on the process indicators. These studies indicate and emphasized on importance of quality control indicators in radiology department.